KOHESI GRAMATIKAL REFERENSI DALAM CERPEN KOMPAS BERBASIS KORTARA - Novela Otri; Syahrul Ramadhan; Tressyalina Tressyalina; Afnita Afnita (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze grammatical cohesion in the form of references in three short stories from the October 2017 edition of Kompas: Sepucuk Amplop di Taman (Envelope in the Garden), Tanah Warisan Asal (Ancestral Heritage Land), and Toko Wong (Wong's Shop). The study focused on the types of grammatical references, such as personal and demonstrative references, used to establish coherence and coherence in the text. A qualitative descriptive approach was used based on the KORTARA corpus (Nusantara Referential Language Corpus) to identify and classify reference forms and their frequency. The analysis showed that the most dominant type of reference was the first-person singular "aku," which strengthens the narrator's position in the story. Meanwhile, demonstrative references such as "ini," "itu," "sini," and "kini" also support the spatial and temporal context of the narrative. This study demonstrates that the use of references not only serves to maintain clarity of reference in the text but also plays a crucial role in forming a cohesive narrative structure. By examining grammatical cohesion through a corpus approach, this research contributes to linguistic studies and Indonesian language teaching, particularly in understanding the interrelationships between sentences in literary discourse. This research also opens up opportunities for further studies examining grammatical cohesion in various other text genres, such as news, essays, or academic texts.